2017
DOI: 10.1038/s41598-017-04759-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Gene Expression in the Uterine Cervix related to Steroid Signaling: Conserved features in the regulation of cervical ripening

Abstract: The uterine cervix is the boundary structure between the uterus and the vagina and is key for the maintenance of pregnancy and timing of parturition. Here we report on a comparative transcriptomic study of the cervix of four placental mammals, mouse, guinea pig, rabbit and armadillo, and one marsupial, opossum. Our aim is to investigate the evolution of cervical gene expression as related to putative mechanisms for functional progesterone withdrawal. Our findings are: 1) The patterns of gene expression in euth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…To test this hypothesis, we measured uterine expression of Fkbp5 and Fkbp4, Pgr and P4 metabolizing enzymes Akr1c18 and Srd5a1 (5α-reductase, which metabolizes P4 to 5α-pregnane-3,20-dione and is primarily expressed in mouse cervix but also in the uterus) (40,41). Consistent with our findings in human decidua ( Fig.…”
Section: Of 12 | Pnassupporting
confidence: 78%
“…To test this hypothesis, we measured uterine expression of Fkbp5 and Fkbp4, Pgr and P4 metabolizing enzymes Akr1c18 and Srd5a1 (5α-reductase, which metabolizes P4 to 5α-pregnane-3,20-dione and is primarily expressed in mouse cervix but also in the uterus) (40,41). Consistent with our findings in human decidua ( Fig.…”
Section: Of 12 | Pnassupporting
confidence: 78%
“…Since circRNAs can activate the transcription of their parental genes, the function of these genes could indirectly reflect the biological impact of circRNAs to some extent (Fischer and Leung, 2017). Among all parental genes of selected circRNAs, CREBBP (the gene of hsa-CREBBP_0001) has been noted to affect the inflammatory signal (NF-κB pathway) of the myometrium, and closely related to labor onset and PTB (Zeng et al, 2008;Wagner et al, 2017). Thus, hsa-CREBBP_0001 was suggested to be associated with PTB by affecting the inflammatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitors have been studied preclinically for use in a variety of inflammatory disorders and have been studied in the context of parturition (40)(41)(42)(43). It has been observed that histone deacetylation increases at term in the myometrium (43) and in the cervix (44,45). Here, we present findings using HDAC inhibitors for the prevention of PTB in a preclinical murine model.…”
Section: Introductionmentioning
confidence: 95%